SOCIAL COMPETENCE AND CULTURALLY RESPONSIVE TEACHING: A STUDY OF SECONDARY SCHOOL TEACHERS IN NAGALAND - Rashmi; Rawat, Neha (International Journal of Research -GRANTHAALAYAH, 2025)
This study investigated the social competence and culturally responsive teaching (CRT) practices of secondary school teachers in Nagaland, India, and examined their interrelationship as well as variations based on gender and teaching experience. A total of 378 teachers participated in the study. Social competence and CRT levels were assessed using z-scores. Findings revealed that while a majority of teachers exhibited average to above-average social competence, a significant proportion demonstrated low or below-average levels. Similarly, the implementation of CRT practices was generally limited, with only a small percentage of teachers demonstrating high levels of culturally responsive pedagogy. Independent-samples t-tests and one-way ANOVAs indicated no statistically significant differences in social competence or CRT based on gender or teaching experience. Importantly, a significant positive correlation was observed between social competence and CRT, suggesting that teachers with stronger interpersonal and relational skills are more likely to engage effectively in culturally responsive teaching. The study underscores the critical role of social competence in enabling culturally responsive pedagogy, particularly in culturally diverse classrooms such as those in Nagaland. Recommendations include targeted professional development, curriculum integration of social-emotional and cultural competencies, mentorship programs, and policy support to enhance inclusive and effective teaching practices.